Determinan Peringkat Obligasi Korporasi - Erna Apriani; Indra Permana (SEIKO : Journal of Management & Business, 2022)
Bonds are one of the company's instruments for obtaining income without going through banks and financial institutions. In 2020, at the beginning of the emergence of the covid-19 pandemic in Indonesia, the issuance of bonds scored a record high for the last five years. This shows that corporations are trying to raise funding through debt securities. During the pandemic, many countries went into lockdown. Of course, this affected corporations whose sales were more than 50% of exports; from this description, the researchers chose mining sector corporations listed on the IDX to analyze how big and influential they are 1). Profitability to bond ratings, 2). Leverage on bond ratings, 3). Coupons against bond ratings, 4). Maturity to bond rating. The method in this study includes the type of applied causality with the type of quantitative analysis that is analytic, the population in this study is the mining sector corporate bonds which are still traded in 2020-2021, with a sample of 45 corporate bonds from 5 mining sector issuing companies, the analytical technique used is ordinal logistic regression, using SPSS 25 analysis tool. The study results conclude that leverage (DER) harms bond ratings, while profitability (ROA), coupons, and maturity do not affect bond ratings. Keywords : Profitability, Leverage, Coupon, Maturity, Bond Rating